TLR22-Induced Pro-Apoptotic mtROS Abets UPRmt-Mediated Mitochondrial Fission in Aeromonas hydrophila-Infected Headkidney Macrophages of Clarias gariepinus - Kumar, Manmohan; Sharma, Shagun; Haque, Munira; Kumar, Jai; Hathi, Umesh Prasad Sah; Mazumder, Shibnath (Frontiers in Immunology, 2022)
Toll-like receptors (TLRs) are epitomized as the first line of defense against pathogens. Amongst TLRs, TLR22 is expressed in non-mammalian aquatic vertebrates, including fish. Using headkidney macrophages (HKM) of Clarias gariepinus, we reported the pro-apoptotic and microbicidal role of TLR22 in Aeromonas hydrophila infection. Mitochondria act as a central scaffold in the innate immune system. However, the precise molecular mechanisms underlying TLR22 signaling and mitochondrial involvement in A. hydrophila-pathogenesis remain unexplored in fish. The aim of the present study was to investigate the nexus between TLR22 and mitochondria in pro-apoptotic immune signaling circuitry in A. hydrophila-infected HKM. We report that TLR22-induced mitochondrial-Ca2+ [Ca2+]mt surge is imperative for mtROS production in A. hydrophila-infected HKM. Mitigating mtROS production enhanced intracellular bacterial replication implicating its anti-microbial role in A. hydrophila-pathogenesis. Enhanced mtROS triggers hif1a expression leading to prolonged chop expression. CHOP prompts mitochondrial unfolded protein response (UPRmt) leading to the enhanced expression of mitochondrial fission marker dnml1, implicating mitochondrial fission in A. hydrophila-pathogenesis. Inhibition of mitochondrial fission reduced HKM apoptosis and increased the bacterial burden. Additionally, TLR22-mediated alterations in mitochondrial architecture impair mitochondrial function (ΔΨ m loss and cytosolic accumulation of cyt c ), which in turn activates caspase-9/caspase-3 axis in A. hydrophila-infected HKM. Based on these findings we conclude that TLR22 prompts mtROS generation, which activates the HIF-1α/CHOP signalosome triggering UPRmt-induced mitochondrial fragmentation culminating in caspase-9/-3-mediated HKM apoptosis and bacterial clearance.